Adjuvant medical therapy provides no therapeutic benefit in the treatment of dogs with low‐grade mast cell tumours and early nodal metastasis undergoing surgery. (17th January 2020) - Marconato, Laura; Stefanello, Damiano; Kiupel, Matti; Finotello, Riccardo; Polton, Gerry; Massari, Federico; Ferrari, Roberta; Agnoli, Chiara; Capitani, Ombretta; Giudice, Chiara; Aresu, Luca; Vasconi, Maria Elisabetta; et al.
Abstract: Lymph node (LN) metastasis is a negative prognostic factor in dogs with cutaneous mast cell tumours (cMCTs). While elective lymphadenectomy of metastatic LNs improves outcome, the benefit of adjuvant medical therapy in dogs with early metastatic (HN2) LNs is debated. The aim of this retrospective multicentre study was to evaluate the therapeutic benefit of adjuvant medical therapy following surgical removal of the primary low‐grade cMCT (Patnaik grade 1‐2 and Kiupel low‐grade) and lymphadenectomy of HN2 LNs by analysing survival rates and patterns of recurrence. Seventy‐three dogs were included: 42 received adjuvant medical treatment (chemotherapy and/or kinase inhibitors), and 31 did not. The median follow‐up time for medically treated dogs was 619 days: two experienced local recurrence, three nodal relapse and four distant relapse. For dogs undergoing surgery only, the median follow‐up time was 545 days. None of them experienced local recurrence, nodal, or distant relapse. Time to progression was significantly shorter in dogs receiving adjuvant medical treatment ( P = .021). A similar tendency was observed for overall survival ( P = .056). The current study shows that dogs with low‐grade cMCTs, that undergo surgical excision of the primary tumour and elective lymphadenectomy of the HN2 regional LN harbour a good prognosis. The use of adjuvant medical treatment in these dogs does not seem to provide any benefit in terms of progression and survival.